Self-efficacy beliefs among English as a foreign language teachers in selected language centers / Farimah Ghasemboland - Ghasemboland, Farimah (2014)
Bandura said that people are self-organizing, proactive, self-reflecting, and self-regulating, and they are not just reactive organisms directed by the environmental events or inner forces. Accordingly, in society the belief that people have in their effectiveness in order to be able to have control over the events in their life is the most important element. If people believe that they can make favorable influences and prevent the unfavorable ones by their performances, they will be motivated enough to act. Bandura (2001) believed that efficacy beliefs affect the way people think either positively or negatively, the kind of aims they would like to achieve and also their commitments to have the results of their efforts. Having high levels of self-efficacy motivates people to have higher goals and as a result they persevere if they face the obstacles or any adverse situation and also they will perform much better. We should remember that self-efficacy is based on a motivational construct and it is the self perception of competence instead of actual level of competence, so actions and behaviors will be better predicted by beliefs instead of actual performance. This study explored the English language center teachers’ self-efficacy in teaching English and its interaction with their reported proficiency level in English, their perceived use of teaching strategies, and their personal background characteristics such as age, gender, level of teaching, years of teaching English, experience traveling or studying abroad, getting IELTS or TOEFL, highest level of education, and type of certificate achieved. The quantitative method of analysis, particularly descriptive and correlational research methods were used in this study. The instruments used in this study consisted of four questionnaires: 1) Teachers’ sense of efficacy in teaching English, 2) Teachers’ reported English language vi proficiency, 3) teachers’ perceived use of teaching strategies, and 4) Teachers’ personal background information. The participants of this research were 187 English teachers in Language schools in 10 different geographical zones of the capital city. The results showed that the variables of this study had low to high correlations with self-efficacy beliefs of the teachers. The results of multiple regressions showed that not all the variables were significant predictors of the self-efficacy beliefs of the teachers of this study. Based on the results of this study some implications were drawn for policy and practice. Additionally, recommendations for future studies were included.